2012
DOI: 10.1016/j.jcrs.2012.05.040
|View full text |Cite
|
Sign up to set email alerts
|

Change in retinal image contrast with age in eyes with transparent lenses

Abstract: Retinal image contrast in eyes with transparent lenses degenerated with age. The decrease was most prominent at the middle frequency domain and was due to the increase in HOAs and light-scattering intensity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…By degrading the spatial resolution of the retinal features, the detection of the vessel lumen and exterior can thus impact measurements of the optical density of the retinal vessels (Mita et al. ). The current conventional approach to retinal oximetry consists of white light illumination of the fundus, where the image is subsequently filtered with light filters for spectrophotometric analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By degrading the spatial resolution of the retinal features, the detection of the vessel lumen and exterior can thus impact measurements of the optical density of the retinal vessels (Mita et al. ). The current conventional approach to retinal oximetry consists of white light illumination of the fundus, where the image is subsequently filtered with light filters for spectrophotometric analysis.…”
Section: Discussionmentioning
confidence: 99%
“…We found that light scatter, which is typical of an ageing lens, can alter retinal vessel oxygen saturation measurements because it can impact the fundus and vessel reflection, which form the basis of the retinal vessel blood oxygen saturation calculation. By degrading the spatial resolution of the retinal features, the detection of the vessel lumen and exterior can thus impact measurements of the optical density of the retinal vessels (Mita et al 2012). The current conventional approach to retinal oximetry consists of white light illumination of the fundus, where the image is subsequently filtered with light filters for spectrophotometric analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This change in ocular media transparency and scattering effect (light diffusion) produced by a cataract can affect both spectral transmission and morphology. By degrading the spatial resolution of the retinal features the detection of the vessel lumen and exterior can thus impact the measurement of optical density of the retinal vessels (Mita et al 2012). Optical density contributes to the calculation of retinal vessel blood oxygen saturation measurements.…”
Section: Introductionmentioning
confidence: 99%